1999
DOI: 10.1002/(sici)1097-4628(19990404)72:1<123::aid-app13>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Self-association through hydrogen bonding and sequence distribution in poly(vinyl acetate-co-vinyl alcohol) copolymers

Abstract: Correlation between hydrogen‐bonding self‐association and sequence distribution in poly(vinyl acetate‐co‐vinyl alcohol) copolymers (ACA) with different degrees of basic hydrolysis and sequence distributions has been studied by thermal analysis and NMR spectroscopy. 13C NMR spectroscopy has also been used to elucidate the blocky nature, branching, and tacticity of the copolymers. Thermal analytical studies indicate that hydrogen bonding distribution in block alcohol and vinyl acetate copolymers strongly depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nuclear Magnetic Resonance. 1 H and 13 C NMR spectra were recorded on a Bruker ARX300 spectrometer using CDCl3 and DMSO solvent for the pure PAS and PVPh-co-PAS copolymers, respectively. Gel Permeation Chromatography (GPC).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Nuclear Magnetic Resonance. 1 H and 13 C NMR spectra were recorded on a Bruker ARX300 spectrometer using CDCl3 and DMSO solvent for the pure PAS and PVPh-co-PAS copolymers, respectively. Gel Permeation Chromatography (GPC).…”
Section: Methodsmentioning
confidence: 87%
“…Earlier studies [7][8][9][10][11][12][13] have found that the copolymers of vinyl alcohol and vinyl acetate (PVA-co-PVAc) prepared from the acidic hydrolysis tend to be more randomly distributed than those obtained from basic solution, suggesting that kinetics of basic hydrolysis of the PVAc is a neighboring group catalytic process superimposed on a general electrostatic effect. Therefore, the probability of hydrolyzing neighboring acetyl groups in basic conditions is significantly higher.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, H-bonds are formed not only between two or more hydroxyl groups but also between an OH group of VA unit and an oxygen atom of VAc unit, in agreement with the literature data. 55,56 From our data, it is not possible to conclude, which of two oxygen atoms in acetyloxy group is preferentially involved into H-bonding and quantum chemistry calculations should be applied here. In any case, if VAc and VA units are chain neighbors, then they can form a hydrogen bond leading to a thermally stable 6-or 8-member ring.…”
Section: ■ Introductionmentioning
confidence: 57%
“…This composition is the most tensile resistant with a force of 182 N and a maximum stress of 73.16 MPa, the most exible (E = 955 MPa) and the most ductile (εr = 768 %). From these results, it can be deduced that the incorporation of the clay into the PVAc matrix, with different percentages, has signi cantly improved all of its tensile properties [48].…”
Section: Mechanical Properties Of Polymermentioning
confidence: 93%